2008
DOI: 10.1002/jcb.21869
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 recruits the histone methyltransferase SUV39H1 for transcription repression

Abstract: EVI1 is an oncoprotein inappropriately expressed in acute myeloid leukemia and myelodysplastic syndrome cells. In vitro studies indicate that diverse biological properties can be attributed to this protein. Its role in leukemogenesis is still unclear but it is thought that overall EVI1 can act mostly as a transcription repressor through its interaction with a subset of histone deacetylases. Studies with histone deacetylase inhibitors have however indicated that EVI1-mediated repression can be only partially re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 40 publications
0
43
2
2
Order By: Relevance
“…21,22 In contrast to these reports, we found that SUV39H1-H324K acts in a dominant-negative manner to abrogate EVI-1-mediated repression of p3TP-Lux reporter activity, whereas wild-type SUV39H1 has little effect on the repression by EVI-1. This discrepancy is probably because of the different cell types and/or promoters used for the assays.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…21,22 In contrast to these reports, we found that SUV39H1-H324K acts in a dominant-negative manner to abrogate EVI-1-mediated repression of p3TP-Lux reporter activity, whereas wild-type SUV39H1 has little effect on the repression by EVI-1. This discrepancy is probably because of the different cell types and/or promoters used for the assays.…”
Section: Discussioncontrasting
confidence: 99%
“…16 In addition, EVI-1 contains a highly acidic domain at the C-terminus, which is required for EVI-1-mediated P-Sp haematopoiesis. 26 In contrast to the earlier reports, which showed that EVI-1 interacts with SUV39H1 through ZF1, 21,22 all of these deletion mutants associate with both SUV39H1 and G9a almost as efficiently as full-length EVI-1 (Figure 2b and c).…”
Section: Roles Of Hmts In Evi-1-mediated Leukemogenesis S Goyama Et Alcontrasting
confidence: 86%
See 2 more Smart Citations
“…2 Interestingly, myeloid malignancies associated with EVI1 overexpression often show dysplastic megakaryopoiesis. 1,6 Although the EVI1 function is not fully understood, recent studies suggest that this gene is involved in chromatin remodeling, through interactions with H3K9 methyltransferases 7,8 Five splice variants of EVI1 have been reported, that is EVI1-1A, -1B, -1C, -1D, and -3L, as well as the MDS1/EVI1 intergenic splice variant. 9,10 The MDS1 gene is located upstream of EVI1 and its function is currently unknown.…”
Section: Introductionmentioning
confidence: 99%